Wastewater Treatment and Reuse Theory and Design Examples, Volume 2: : Post-Treatment, Reuse, and Disposal - Qasim, Syed R.; Zhu, Guang (Boca Raton, FL : CRC Press, 2017)
"This book will present the theory involved in wastewater treatment processes, define the important design parameters involved, and provide typical values of these parameters for ready reference; and also provide numerical applications and step-by-step calculation procedures in solved examples. These examples and solutions will help enhance the readers' comprehension and deeper understanding of the basic concepts, and can be applied by plant designers to design various components of the treatment facilities. It will also examine the actual calculation steps in numerical examples, focusing on practical application of theory and principles into process and water treatment facility design."--Provided by publisher.
chapter Half Title -- chapter Title Page -- chapter Copyright Page -- chapter Contents -- chapter Preface -- chapter Acknowledgment -- chapter Authors -- chapter 11 Disinfection -- chapter 12 Effluent Reuse and Disposal -- chapter 13 Residuals Processing, Disposal, and Reuse -- chapter 14 Plant Layout, Yard Piping, Plant Hydraulics, and Instrumentation and Controls -- chapter 15 Advanced Wastewater Treatment and Upgrading Secondary Treatment Facility.
Keywords: Ecology -- Environment Studies; ENVIROnetBASE; ENVIRONMENTALENGINEERINGnetBASE; ENVIRONMENTALSCIENCEnetBASE; SCI-TECHnetBASE.; Ecology - Environment Studies; ENVIROnetBASE; ENVIRONMENTALENGINEERINGnetBASE; ENVIRONMENTALSCIENCEnetBASE; SCI-TECHnetBASE; STMnetBASE; Waste & Recycling; Water Science; WATERnetBASE